OBD-II vehicle data capture and monitoring system prototype - Aciti, Claudio (2018)
In this work, a prototype of a system for capturing vehicle parameters according to OBD-II technology was designed and built. The prototype is able to read different magnitudes generated by a car through an ELM-327 USB interface that allows communication with the vehicle on-board computer, and the data obtained through a USB GPS. A 3G modem and a USB Wifi adapter were added to the developed prototype. The system was implemented on a Raspberry Pi B platform with the Raspbian operating system. The 3G modem was used to transmit information collected over the Internet to a remote device or exchange. The USB WiFi adapter allowed the Raspberry Pi to be configured as an Access Point. In this way, it could be connected to a mobile device that supports the Android operating system to visualize the data read. The tests were conducted on a Chevrolet Corsa Wagon Life Gls 1.4 4p model 2009.